The Principles of Good Government in Suppressing Corruption - Handitya, Binov (Law Research Review Quarterly, 2019)
This paper discusses the application of The Principles Of Good Government, or what we often know with the General Principles of Good Governance (AUPB) in the implementation of government policies, needs to be improved. As a form of filter that is able to filter out any government administration so that it can be free from the snare of corruption. Public officials or implementers must be emphasized in understanding in depth the principles contained in the AUPB to be applied in providing services to the public / community. There are at least 8 (eight) principles attached to the AUPB based on the Government Administration Law, among others: the principle of legal certainty, the principle of expediency, the principle of impartiality, the principle of accuracy, the principle of not abusing authority, the principle of openness, the principle of public interest and the principle of good service.